Enhancing Knowledge Transfer Experience Through Computer-Aided Design, Virtual Learning Environment and Community Engagement - Yusvana, Rama; Roslinazairimah, Zakaria; Wan Nurhafisya, Mior Norazmi; Farahanim, Misni (ICKT 2015, 2016)
Knowledge Transfer Program for the construction and maintenance of integrated farming utilizing aquaponics system has been conducted between Universiti Malaysia Pahang, the local school community partner (Al-Irsyad Islamic School) and science school Sultan Haji Ahmad Shah, Kuantan. The knowledge transfer approach was a blending between the use of Computer-Aided Design (CAD), Virtual Learning Environment (VLE) and active (hands-on) participation of the university students and community members to enhance the knowledge transfer experience. Teachers, school students and university final year industrial biotechnology students have participated in the program. The trainer used a free 3D design Google Sketch Up to enhance spatial (3D) understanding of the students in the essential components of the device and the working mechanism. The trained university students were also assessed using Moodle internet-based Virtual Learning Environment (VLE) that has been actively used by academics in UMP. Subsequently, the final year university students applied the knowledge they have learned and trained during the weeks by engaging the local school students in the Knowledge Transfer Program activities (workshops). A total of fifty-six (56) university students have engaged and trained 98 secondary school students (47% female, 53% male) with age from 13 years old (26%) to above 16 yearsold (13%). It shows that 93% of the students agreed to have received new skills (basic aquaponics system construction) by this outdoor and hands-on Knowledge Transfer activities, conducted by the senior (university) students. The data also indicated that 82% of the students have an increased appreciation to science due to the application and peer-demonstration of the system. From the video recorded, the school students were able to construct aquaponics system in a team environment without receiving further assistance. This indicates that hands-on and teamwork constructions of a product or technology have significant impacts to the cognitive learning (understanding) in Knowledge Transfer activities.